Using remote sensing indicators to investigate the association of landings with fronts: Application to the Alboran Sea (western Mediterranean Sea). (2nd March 2018) - Brigolin, D.; Girardi, P.; Miller, P. I.; Xu, W.; Nachite, D.; Zucchetta, M.; Pranovi, F.
Abstract: This study examined links between the variability of coastal front features and composition of fishery landings. Satellite‐derived sea surface temperature data allowed the detection of thermal fronts and calculation of front metrics that account for gradient, persistency, and vicinity. Landings data were clustered by functional group (according to habitat use, size, morphology), and trophic level (TL). Three independent time series analyses, based on two different classes of statistical methodologies, were carried out: (i) correlation analysis performed on species aggregated by functional groups, and (ii) compositional analysis performed on the top five species landed and on species aggregated by trophic level. Analyses were carried out for the Moroccan coast of the Alboran Sea (western Mediterranean Sea). Results of the proposed type of application were discussed with respect to their potential for improving scientific knowledge and management of fisheries in data‐poor areas. Pelagic landings were associated with front indicators in two‐thirds of tested cases. The results demonstrated a markedly different association between landings and front features in the Nador fishing zone, relative to M'diq and Al Hoceima. Improved performance of the front gradient and persistence indicator was detected, with respect to the front gradient only for flatfish and demersal landings. Compositional data regression outlined a different role for Sardina pilchardus and Trachurus trachurus in the Al Hoceima and M'diq landings, and in the latter case the dominance of these two species in the landings seemed to respond to the front density indicator. A decreasing trend in TL > 3.5 landings was detected with increasing front distance.